Developing a high strength physico-mechanical and electrical properties of ceramic porcelain insulator using zirconia as an additive. (13th July 2018) - Mehta, Niraj Singh; Pandey, J C; Pandey, Neeraj; Pyare, Ram; Majhi, Manas Ranjan
Abstract: In this article, the effects of sintering on the mechanical and electrical properties of ceramic porcelain insulator reinforced by zirconia (ZrO2 ) particles are studied for the low frequencies (20 Hz–1 MHz). The samples were prepared for varying contents of zirconia by replacing alumina content in the base porcelain composition. The samples are sintered at 1250 °C and 1350 °C with a heating rate of 5 °C min −1 and the soaking period is 2 h. The β -cristobalite phase of base porcelain decreases and the crystalline phase of zircon increases with the increasing sintering temperature. This improvement in crystallite phase of zircon improves the mechanical strength of the reported samples. The sample with zirconia content of 20 wt% sintered at 1350 °C shows the best mechanical properties with minimum water absorption of 0.89%. The highest measured value for modulus of rupture (MOR), compressive strength, and linear shrinkage are 138 ± 5 MPa, 221 ± 10 MPa, and 10.6%, respectively. The sample with zirconia content of 30 wt% sintered at 1350 °C shows the best electrical properties among all samples. Maximum observed value for AC dielectric strength of the sintered sample is 22.85 ± 0.5 KV mm −1 . The measured AC conductivities of samples are 3.88 × 10 −12 S cm −1 and 1.41 × 10 −9 S cm −1 at 500 Hz and 1 MHz respectively. The complex permittivity's of the sintered samples are found to be dependent on contents of ZrO2 and also exhibit a frequency dependent characteristics for a range of frequency (20 Hz to 1 MHz). The result indicates that variation in ZrO2 composition leads to significant improvements in mechanical and electrical properties of porcelain ceramic.